Relationship between STK39 Genotype and Vitamin D3 in Hypertension - Zahraa Sabbar Omran (Journal of Global Pharma Technology, 2018)
Vitamin D is a lip soluble molecule obtained through exposure to sunlight and intake of foods containing this nutrient naturally. A diet deficient in vitamin D3 in conjunction with inadequate sun exposure causes osteomalacia, the study was designed to relation between STK39 genotype and vitamin D3 in hypertensive, In study included 70 hypertensive patients with no signs and symptoms of renal impairment and another 30 control subjects .The links between genotype and vitamin D3 in hypertension were examined. The results showed that there were Vitamin D3 deficiency is present in 82.2% of the female hypertension group compared with 17.8% in control group, and There is a significant association between STK39 genotype and 25 (OH)D3 at (p=0.02) particularly in males .